Pengaruh Independensi, Tingkat Pemahaman Akuntansi, Dan Pengalaman Kerja Terhadap Kinerja Pengawas Lembaga Perkreditan Desa (LPD) Se-Kecamatan Payangan - Anak Agung Istri Putri Amala Dewi; I Wayan Budi Satriya (Hita Akuntansi dan Keuangan, 2023)
ABSTRACT In achieving the vision and mission and minimizing fraud in a village credit institution (LPD) a good management system is needed. Therefore, in achieving the goals of the village credit institution (LPD), optimal supervisory performance is needed so that no fraud occurs. Supervisory performance is the result of work achieved by a supervisor in an organization in accordance with the authority and responsibility of a supervisor. This study aims to determine the effect of Independence, Accounting Understanding Level, and Work Experience on the Performance of Supervisors of Village Credit Institutions (LPD) in Payangan District. The population in this study was all LPD supervisors in Payangan District, totaling 29 LPDs, with a total population of 70 supervisors. The number of samples in this study were 70 people who were determined by saturation sampling technique and tested using multiple linear regression analysis techniques. The results of this study indicate that Independence, Accounting Understanding Level and Work Experience have a positive and significant effect on the performance of LPD supervisors in Payangan District. The results of this study can be used as material for consideration in designing policies related to performance improvement. In the future, supervisors must improve the performance of supervisors by increasing the attitude of independence, the level of understanding of accounting and work experience.